Uterine Pathology and Physiology in the Post Partum Period in Ethiopian Cattle - Källerö, Emma Elisa (2010)
The study was performed at a specialized commercial dairy farm; Holetta Agricultural Research Centre (HARC) located 40 km west of Addis Ababa in Ethiopia. Here pure Borana and crossbred Borana x Holstein-Friesian are kept. The postpartum functions were monitored using rectal palpation as well as ultrasonography. The extent of bacterial contamination of the uterus was examined using uterine swabs for subsequent culturing. To obtain a comprehensive picture of the cows’ health status traditional clinical examination including examination of the vaginal mucus were used. In addition to this, cow signals were used as a basis for forming a general judgement of the cows’ health. The main objectives were to gain deeper knowledge of the uterine pathophysiology during the post partum period in Borana and Borana x Holstein crossbreeds, to compare them with another as well as with high-producing breeds of cattle. The results showed that the uterine involutionary process was similar in Boranas, Borana x Holstein crossbreeds and to that of high-producing breeds. The Boranas presented a higher percentage of uterine bacterial contamination and the Borana x Holstein crossbreeds a lower percentage than that of high-producing cattle. The bacterial findings were similar so the flora found in high-producing breeds. Vaginal mucus evaluation appeared to be an uncertain method for evaluating bacterial findings in the uterine lumen. The results also showed that the body condition during the post partum period was mildly decreased in the Boranas and had increased in the crossbreeds. This is remarkable when comparing with high-producing breeds, which exclusively enters a negative energy balance. Conclusively the low level of production in the Boranas and the crossbreeds protect them from entering a negative energy balance.